SUPREMASI KONSTITUSI ADALAH TUJUAN NEGARA - Johannes Suhardjana (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Contitution or Fundamental norms is the supreme law governing the operation of the working rules of the state as an organization, so that the constitution would give the direction and under the laws and regulation. In the constitution there must be an effective system, regularly to the mechanism or the operations of the government and the main of the constitutions is the existence of restriction of the authority and respect for the human rights, because human rights is human nature that possesses from birth.Keywords: constitution, restriction, human rights